Phage-derived Hol49_Lys19/sodium alginate/chitosan composite green coating: Preparation, performance and preservation effect on refrigerated salmon - Shuxuan Li; Jing Li; Ming Zhang; Rundong Wang; Xiaoni Wang; Chunyan Li; Defu Zhang (Food Microbiology, 2027)

High-precision extraction and dynamics of thermokarst lakes in the Three Rivers Source Region using the SVM coupled edge-OTSU based on Sentinel-1 data - Wangping Li; Rongqi Wan; Xiaodong Wu; Xiaoqiang Cheng; Yadong Liu; Yanjun Bian; Heng Du; Niu Wang; Wenbo Wei; Zhaoye Zhou; Xiuxia Zhang; Defu Zou (CATENA, 2026)

Elevated hydrostatic pressure promotes organic carbon mineralization in reservoir sediments - Yan Zhang; Shangbin Xiao; Defu Liu; Wenjun Yang; Huiqun Cao; Jia Liu; Chenghao Wang; Li Zhu; Shijian Li; Shiping Lai; Xinghui Xia (Water Research, 2026)

Physics-informed machine learning of hyporheic exchange driven by channel blockage and riverbed morphodynamics - Hang Li; Linlin Li; Defu Liu; Genguang Zhang; Jiahao Zou; Yu Lei; Canyong Li (Journal of Hydrology, 2026)

Characterization of the overall quality, flavor compounds, sensory analysis, and microbial community of huangjiu co-fermentation with Rhodotorula mucilaginosa and Saccharomyces cerevisiae - Mengzhu Yu; Changpeng Li; Gaopo Li; Defu Zhang; Zhangyi Feng; Dongliang Reng; Jun Qiu; Song Fang; Yuzong Zhao (Food Research International, 2026)

Parameterization of ground ice dynamics in permafrost models: Advances, challenges, and future directions - Yifan Wu; Guojie Hu; Lin Zhao; Zhe Sun; Bowen Zhang; Yao Xiao; Defu Zou; Guangyue Liu; Xiaofan Zhu; Tonghua Wu; Xiaodong Wu; Wenxin Zhang; et al. (Earth-Science Reviews, 2026)

Remediation of Black and Odorous Water using a Slow-release Composite Agent Containing CaO2, Zeolite, and Polymeric Ferric Sulfate: Effects on Water Quality and Chlorella Growth - Jinhai Li; Defu Xu; Yafei Xun; Ying Zhuang; Meiling Guan; Alan Howard (Water, Air, & Soil Pollution, 2026)

Enhanced catalytic activity in ion-doped CeO2 via lattice distortion engineering for diketone hydrogenation - Defu Yin; Lu Shen; Xinjun Feng; Shitao Yu; Lu Li; Shiwei Liu; Sai Geng; Yue Liu (Chemical Engineering Journal, 2026)

Soil texture regulates soil C mineralization by C substrates and microbial characteristics under vegetation restoration - Lingbo Dong; Weifang Hu; Defu Wang; Hailong Zhang; Jianzhao Wu; Jiwei Li; Rula Sa; Zhouping Shangguan; Lei Deng (Plant and Soil, 2026)

Experimental Investigation into the Influence of Water Saturation on the Tensile Failure Behavior of Diaspore-Type Bauxite: Implications for Underground Mining of Bauxite - Defu Zhu; Wenshuo Hu; Yalin Li; Qingsheng Bai; Yongjie Jia; TengFei Fu; Gan Feng; Yujiang Zhang; Xiaosong Sun; Yongqing Lin; Dingwei Sun (Rock Mechanics and Rock Engineering, 2026)

Multi-component dissolved gas dynamics as early warning indicators for algal bloom development in the three gorges reservoir - Chenyu Wei; Dian Li; Hao Li; Yanan Huang; Xiaojuan Guo; Hao Zhang; Danli Deng; Defu Liu; Zhengjian Yang (Water Research, 2026)

Zinc-reinforced sandwich-structured nano-magnesium oxide composite collagen barrier membrane for promoting bone regeneration - Hong Du; Shasha Lei; Jianhui Wu; Yiruo He; Lun Yuan; Liming Ge; Changdao Mu; Zhilang Xu; Defu Li (Chemical Engineering Journal, 2026)

In-situ radical polymerization for solid polymer electrolytes in lithium-ion batteries: a comprehensive review - Yong Luo; Churu Zhang; Ya Liao; Zhitian Ding; Defu Li; Lufa Zhu; Hao Luo; Beiyuan Liu; Jiali Guo; Xiaoli Peng; Shipai Song; Yong Xiang; et al. (Chemical Engineering Journal, 2026)

Gp8 mediates adsorption of bacteriophage vB_VpP_jzsmvpa to the host Vibrio parahaemolyticus - Shuxuan Li; Xiaoni Wang; Jing Li; Ming Zhang; Ke Liu; Xuepeng Li; Jianrong Li; Chunyan Li; Defu Zhang (Antonie van Leeuwenhoek, 2026)

Near-surface ground ice map of the Northern Hemisphere - Bingquan Wang; Youhua Ran; Xin Li; Jan Hjort; Olli Karjalainen; Qingbai Wu; Yu Sheng; Huijun Jin; Defu Zou; Lin Zhao; Rui Ma; Ziyong Sun; et al. (Science Bulletin, 2026)

The crucial role of ground ice in slowing permafrost degradation - Guojie Hu; Zhe Sun; Lin Zhao; Deliang Chen; Defu Zou; Chien-Lu Ping; Wenxin Zhang; Yao Xiao; Guangyue Liu; Ren Li; Xiaodong Wu; Yifan Wu; et al. (Science Bulletin, 2026)

Benchmarking and lightweight correction of daily near-surface air temperature products over the Qinghai-Tibetan Plateau - Nan Zhou; Yao Xiao; Lin Zhao; Guojie Hu; Lingxiao Wang; Chong Wang; Ren Li; Guangyue Liu; Defu Zou; Xiangfei Li (Atmospheric Research, 2026)

Autotrophic denitrification filter prepared using gasification coarse slag and pyrite: Physicochemical characteristics and performance removal of nitrogen - Shuhan Yang; Defu Xu; Jing Su; Zhengxuan Li; Alan Howard (International Biodeterioration & Biodegradation, 2026)

High-resolution (30 m) mapping of permafrost distribution in the Genhe River Basin, Greater Khingan Mountains, Northeast China - Xueling Jiao; Lin Zhao; Defu Zou; Lingxiao Wang; Chong Wang; Yuanwei Wang; Guojie Hu; Erji Du; Yao Xiao; Guangyue Liu; Shibo Liu; Yuxin Zhang; et al. (Journal of Mountain Science, 2026)

Effect of palladium loading on catalytic performance and product selectivity during diclofenac degradation by Pd0@anaerobic activated sludge - Xiaodi Li; Jingzhou Zhou; Lin Yang; Si Pang; Yi Yang; Defu Gan; Junxia He; Penghui Shi; Siqing Xia (Journal of Cleaner Production, 2026)

Multifactorial impacts on ash behaviors during oxy-fuel co-combustion of semi-coke and biomass - Jinping Zhang; Wenwen Wei; Haichen Zhao; Siyuan Li; Jingchun Shen; Defu Che; Lei Chen (Fuel, 2026)

Comparative study on microwave and conventional pyrolysis characteristics of Tar-Rich coal - Xiaole Huang; Xing Ning; Jingwen Mao; Peiqi Li; Jiyun Ren; Qidong Yang; Lei Deng; Defu Che (Fuel, 2026)

Ctab-mediated core-shell Pd-based nanocatalysts: pore engineering and N-doping synergy for efficient phenol hydrogenation to cyclohexanone - Lu Shen; Defu Yin; Zewei Hu; Dongyu Liu; Shitao Yu; Lu Li; Shiwei Liu; Yue Liu (Fuel, 2026)

NO heterogeneous reduction during oxy-fuel combustion of semi-coke: The role of high-temperature rapid gasification - Pengqian Wang; Chenxi Zhang; Xingpeng Li; Jiaojiao Zhang; Yi Liu; Yongbo Du; Chang’an Wang; Defu Che; Bo Bai (Fuel, 2026)

Retraction notice to “Targeted delivery of honokiol by zein/hyaluronic acid core-shell nanoparticles to suppress breast cancer growth and metastasis” [Carbohydr. Polym. 240 (2020) 116325 - Qi Zhang; Jing Wang; Dan Liu; Wenquan Zhu; Shuang Guan; Li Fan; Defu Cai (Carbohydrate Polymers, 2026)

In situ acoustic quantification of methane ebullition in Xiangxi Bay, Three Gorges Reservoir - Chenyu Wei; Zhengjian Yang; Dian Li; Yanan Huang; Xiaojuan Guo; Defu Liu (Environmental Monitoring and Assessment, 2025)

Control of backfill ratio in a short-wall green-intelligent mining working face to prevent pollution from coal-based solid waste: experimental and design studies on the relationship between two-dimensional images and volume of gangue - Yun Zhang; Yixuan Yang; Xingping Lai; Shenggen Cao; Yongzi Liu; Mingbo Chi; Defu Zhu; Baiyi Li; Di Wang; Jifeng Li (Journal of Cleaner Production, 2025)

Redox diverse Co+2/Co+3 species embedded 3D nanoconfined silica walls as an efficient catalyst for fast oxidative desulfurization of fuel oil - Mateen Ahmad; Usman Ali; Afaq Nazir; Xiaoqi Liu; Haoran Sun; Haonan Zhang; Defu Yin; Alieu Kamara; Hanbao Li; Zhen Liu; Zifeng Yan (Fuel, 2025)

Corrigendum to “Hyaluronic acid-modified liposomal honokiol nanocarrier: Enhance anti-metastasis and antitumor efficacy against breast cancer” [Carbohydr. Polym. 235 (2020) 115981] - Jing Wang; Dan Liu; Shuang Guan; Wenquan Zhu; Li Fan; Qi Zhang; Defu Cai (Carbohydrate Polymers, 2025)

Quantifying the soil water content of the permafrost active layer using InSAR deformation - Erji Du; Lingxiao Wang; Lin Zhao; Huayun Zhou; Shibo Liu; Defu Zou; Guangyue Liu; Yao Xiao; Guojie Hu; Zhibin Li; Junqiang Gao; Chong Wang; et al. (Journal of Hydrology, 2025)

Research and Application of the Calculation Method for Vertical Stress of Interlayer Rock in Coal Mining Under Pillar Goaf - Qian Wang; Yujiang Zhang; Guorui Feng; Defu Zhu; Fudong Ma; Wushuai Hao; Shule Li; Shuai Zhang (Rock Mechanics and Rock Engineering, 2025)

Preliminary analysis of a slow-moving high-locality landslide in the Zagunao River Basin, Sichuan Province, China - Shengsen Zhou; Weile Li; Huiyan Lu; Zhou Xu; Wenlong Yu; Shanmiao Xu; Pan Zhang; Chunhao Wei; Yusen Li; Defu Wang; Weiwei Zhan; Qiang Xu (Bulletin of Engineering Geology and the Environment, 2025)

A probabilistic formula for sediment incipient motion on combined sloping beds by considering the hiding-exposure effect - Linlin Li; Hang Li; Genguang Zhang; Yao Xiao; Defu Liu; Yu Lei; Maohua Le (Hydrological Sciences Journal, 2025)

Characterization of volatile flavour compounds and characteristic flavour precursors in poultry eggs based on multi-omics and machine learning - Hongqiang Li; Xiangmin Zhao; Xiaoming Li; Jing Liang; Shizhen Qin; Jinlu Li; Aiwen Zhang; Linna Xu; Defu Tang; Fuwei Li (Food Chemistry, 2025)

Threshold-governed insulating and cooling effects of snow cover on alpine permafrost: evidence from the Qinghai–Tibet Plateau - Yao Xiao; Guojie Hu; Ren Li; Tonghua Wu; Xiaodong Wu; Guangyue Liu; Defu Zou; Zanpin Xing; Jimin Yao; Chong Wang; Lin Zhao (Agricultural and Forest Meteorology, 2025)

A coupled model of surface water-groundwater interaction with the effect of riverbed deformation in the alluvial channel - Linlin Li; Hang Li; Genguang Zhang; Defu Liu; Yao Xiao; Ying Liu; Jiahao Zou (CATENA, 2025)

Preparation of carbon nanosheet from molten salts assisted pyrolysis of biomass towards to carbon-negative technology - Sunwen Xia; Chen Zhang; Rui Fang; Yong Wang; Defu Shi; Bin Li; Dong Wang; Kuihua Han; Haiping Yang (Fuel, 2025)

Promising eco-friendly agents targeting Pseudomonas fluorescens biofilms - Xiaoli Chen; Defu Zhang; Xuefei Liu; Jianrong Li; Lu Wang; Xue Bai (Food Bioscience, 2025)

Research on Ship Engine Fuel Consumption Prediction Algorithm Based on Adaptive Optimization Generative Network - Defu Zhang; Yuxuan Song; Jianfeng Gao; Zhenyu Shen; Liangkuan Li; Anren Yao (Journal of Marine Science and Engineering, 2025)
With the long-term operation of ships, the performance of marine diesel engines gradually declines due to the wear of internal moving components, increasing the risk of potential failures. Fuel consumption is a critical indicator for assessing engine operating conditions, and accurately predicting baseline fuel consumption under normal operating conditions is essential for evaluating ship energy efficiency and conducting fault diagnosis. To address common issues in marine engine operational data, such as noise pollution, missing values, inconsistent scales, and feature redundancy, a Diesel Engine Data Enhancement and Optimization Framework (DEOF) was developed to systematically improve data quality. Furthermore, to overcome the limitations of existing models, such as insufficient prediction accuracy and poor stability under complex operating conditions, a Meta-learning Diffusion Residual Attention Network (MD-RAN) is proposed. This approach leverages the strengths of diffusion models in nonlinear generative modeling, integrates meta-learning mechanisms to enhance task adaptation speed, employs multi-head attention modules to strengthen feature extraction, and incorporates dynamic residual connections to improve training stability and flexibility. The data used in this study were collected from real-world operations of ocean-going vessels, ensuring high representativeness. This paper systematically benchmarks the proposed model with the traditional learning model. The results are verified to be effective. The MD-RAN algorithm is significantly better than the original model in terms of prediction accuracy, stability, and nonlinear expression ability. The R2 value can reach 0.9853, and the RMSE and MAE are as low as 1.5801 and 1.1879, respectively. Its feasibility will be further evaluated in practical applications in the future. This study not only provides a systematic data-driven modeling framework, offering technical insights for constructing high-quality datasets, but also establishes a novel generative modeling approach for marine diesel engine fuel consumption prediction, providing robust support for intelligent engine maintenance and energy efficiency optimization.

Preparation and application of bioadhesive hydrogel powder loaded with quorum sensing inhibitor isomaltitol for salmon preservation - Ke Liu; Ming Zhang; Wutong Bai; Wenjing Yang; Xinran Lv; Xue Bai; Xuepeng Li; Defu Zhang; Jianrong Li (Food and Bioproducts Processing, 2025)

Simulation investigation on separation characteristics of gas-liquid model products from in-situ pyrolysis of tar-rich coal - Tianlin Yuan; Chang’an Wang; Meijing Chen; Fu Yang; Yujie Hou; Li Ma; Zhonghui Duan; Defu Che (Journal of Environmental Chemical Engineering, 2025)

Optimization of enzymatic hydrolysis of collagen and screening and application of hypolipidemic peptide - Yancheng Bi; Ming Zhang; Ke Liu; Xinran Lv; Xuepeng Li; Xue Gao; Fangchao Cui; Defu Zhang; Jianrong Li (Food Bioscience, 2025)

Modeling of sediment exchange process and channel evolution in the downstream reach below the Three Gorges Dam - Linlin Li; Junqiang Xia; Meirong Zhou; Shanshan Deng; Defu Liu; Hang Li; Yu Lei (CATENA, 2025)

Targeted phytogenic compounds against Vibrio parahaemolyticus biofilms - Xue Bai; Xiaoli Chen; Defu Zhang; Xuefei Liu; Jianrong Li (Critical Reviews in Food Science and Nutrition, 2025)

Retrieval of 1 km surface soil moisture from Sentinel-1 over bare soil and grassland on the Qinghai-Tibetan Plateau - Zanpin Xing; Lin Zhao; Lei Fan; Gabrielle De Lannoy; Xiaojing Bai; Xiangzhuo Liu; Jian Peng; Frédéric Frappart; Kun Yang; Xin Li; Zhilan Zhou; Xiaojun Li; et al. (Remote Sensing of Environment, 2025)

PdH as the hydrogen transporter for phenol hydrogenation reaction - Defu Yin; Zewei Hu; Yunxi Hou; Shitao Yu; Lu Li; Shiwei Liu; Yue Liu (Chemical Engineering Journal, 2025)

Bacterial community structure and metabolomic profiles of yak milk and cattle-yak milk during refrigeration in Gannan region: Analysis of interspecific differences in milk spoilage - Hongqiang Li; Hongbo Wang; Yaqin Gao; Xiangmin Zhao; Jing Liang; Longying Pei; Yali Yao; Defu Tang (Food Chemistry, 2025)

Multi-indicators environmental impact analysis of takeaway lunch boxes based on life cycle assessment - Xinyu Cui; Yu Zhao; Xin Guo; Lijiang Huo; Defu Li (Environmental Research, 2025)

Threshold of sediment incipient motion on a three-dimensional riverbed by considering the hiding-exposure effect with experimental investigations - Linlin Li; Yao Xiao; Genguang Zhang; Yu Lei; Hang Li; Defu Liu (Acta Geophysica, 2024)

Cascaded reservoirs promote phosphorus bioavailability of surface sediments in the Upper Mekong River - Zhengjian Yang; QiFeng Min; Xiaojuan Guo; Congfeng Wang; Bi'’e Yan; Xiaoling Li; Defu Liu; Jun Ma; Andreas Lorke (Science of The Total Environment, 2024)

Spatiotemporal changes and management measure to enhance ecosystem services in the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Yadong Liu; Xuchun Yan; Xiaoying Fan; Avirmed Dashtseren; et al. (Environmental Development, 2024)

Enhancing biofilm formation with powder carriers for efficient nitrogen and phosphorus removal - Yi Yang; Yuting Zhu; Defu Gan; Xiang Cai; Xiaodi Li; Xinchao Liu; Siqing Xia (Science of The Total Environment, 2024)

Binding between Cu2+/Zn2+ and aged polyethylene and polyethylene terephthalate microplastics in swine wastewaters: Adsorption behavior, and mechanism insights - Mengyu Ma; Ruxin Han; Ruoqi Han; Defu Xu; Feihu Li (Environmental Pollution, 2024)

Experimental investigation on product and temperature distribution in a continuous flow packed-bed reactor for dodecahydro-N-ethylcarbazole dehydrogenation - Jingwen Xue; Pengzhao Li; Pengfei Yu; Jinhao Yi; Tao Ma; Hu Liu; Defu Che (Chemical Engineering Journal, 2024)

Large variability in permafrost degradation over the Northern Hemisphere - Guojie Hu; Lin Zhao; Defu Zou; Xiaodong Wu; Ren Li; Xiaofan Zhu; Youqi Su; Tonghua Wu; Yifan Wu; Jie Ni (CATENA, 2024)

Injectable NGF-loaded double crosslinked collagen/hyaluronic acid hydrogels for irregular bone defect repair via neuro-guided osteogenic process - Qingsong Jiang; Liaomin Zhou; Yi Yang; Hu Long; Liming Ge; Defu Li; Changdao Mu; Wenli Lai; Zhilang Xu; Yan Wang (Chemical Engineering Journal, 2024)

Simultaneous hydroxyapatite-based phosphorus recovery and partial denitrification-anammox-based nitrogen removal during sludge leachate treatment - Ben Dai; Yifeng Yang; Zuobin Wang; Jingzhou Zhou; Xiaodi Li; Yi Yang; Defu Gan; Junxia He; Xin Zhang; Siqing Xia (Journal of Water Process Engineering, 2024)

A practical study on the near-zero discharge of rainwater and the collaborative treatment and regeneration of rainwater and sewage - Yi Yang; Wenlong Bai; Defu Gan; Yuting Zhu; Xiaodi Li; Chengyu Liang; Siqing Xia (Science of The Total Environment, 2024)

Biogenic palladium nanoparticles for wastewater treatment: Formation, applications, limitations, and future directions - Xiaodi Li; Lin Yang; Jingzhou Zhou; Ben Dai; Defu Gan; Yi Yang; Zhenyu Wang; Junxia He; Siqing Xia (Journal of Water Process Engineering, 2024)

Influence of point bars on nitrogen transport and reaction in riparian zones - Xunchuan Song; Ying Liu; Defu Liu; Jinghong Feng; Linlin Li; Yongsheng Guo; Junxiong Luo; Weiping Jiang (Journal of Hydrology, 2024)

In situ green immobilization of palladium nanoparticles onto polydopamine-modified eggshell membrane for catalytic reduction of nitrophenols - Yi Yang; Defu Gan; Xiaodi Li; Jingzhou Zhou; Lin Yang; Ben Dai; Siqing Xia (Journal of Water Process Engineering, 2024)

Experimental study on metal removal characteristics of Zhundong coal to produce ultra-clean coal using acid-alkali method - Yuanmao Chen; Chang'an Wang; Yang Li; Maoyun Luo; Chenglong Yang; Lin Zhao; Zhefan Wang; Ning Fu; Defu Che (Fuel, 2024)

Electric-field-controlled energy barrier and reaction pathway ensure high sulfur product selectivity in Cu/γ-Al2O3 catalyst-assisted DBD plasma conversion of carbonyl sulfide - Yixing Ma; Peng Chen; Defu Li; Fei Wang; Langlang Wang; Kai Li; Ping Ning; Xueqian Wang; Kostya (Ken) Ostrikov (Journal of Environmental Chemical Engineering, 2024)

New insight into oxygen vacancy and synergism in CuCeOx catalysts based on the toluene oxidation - Guangtao Hu; Zirui Zhang; Chang’an Wang; Guojie Li; Dandan Zhou; Jinshi Wang; Defu Che; Running Kang (Journal of Environmental Chemical Engineering, 2024)

Exploring the link between microbial community structure and flavour compounds of traditional fermented yak milk in Gannan region - Hongqiang Li; Xiaoling Yang; Defu Tang; Bin Xi; Weihong Li; Zhaohui Chen; Yongqing Bao; Renqing Dingkao; Yaqin Gao; Peng Wang; Hongbo Wang (Food Chemistry, 2024)

Highly stereoselective hydrogenation of α‑pinene over Ir nanoparticles confined in SiO2 shells - Defu Yin; Zewei Hu; Mingya Liu; Jingyun Zhang; Hanli Zheng; Yunxi Hou; Shitao Yu; Lu Li; Shiwei Liu; Yue Liu (Chemical Engineering Journal, 2024)

Quantitative Proteomics Reveals Manganese Alleviates Heat Stress of Broiler Myocardial Cells via Regulating Nucleic Acid Metabolism - Shizhen Qin; Rui Wang; Jinlu Li; Defu Tang; Zhaoguo Shi (Biological Trace Element Research, 2024)

Characteristic of geopolymer modified by MgO and its adsorption capacity of phosphate and ammonium ions from swine wastewater - Shuaishuai Li; Defu Xu; Die Wu; Alan Howard (Process Safety and Environmental Protection, 2024)

Enhanced removal efficiency of nitrogen and phosphorus from swine wastewater using MgO modified pig manure biochar - Liuying Wu; Defu Xu; Bing Li; Die Wu; Hong Yang (Journal of Environmental Chemical Engineering, 2024)

Catalytic gasification of large particle-size biomass with loaded AAEMs under oxygen-steam atmosphere - Jiyun Ren; Kaixuan Yang; Yuhang Li; Yang Bai; Jiahao Jiang; Xiaole Huang; Lei Deng; Defu Che (Fuel, 2024)

The evolutionary adaptation of shrimp hemocyanin subtypes and the consequences on their structure and functions - Jiaxi Li; Mingming Zhao; Xin Zhang; Zhihong Zheng; Defu Yao; Shen Yang; Ting Chen; Yueling Zhang; Jude Juventus Aweya (Fish & Shellfish Immunology, 2024)

Use of a new Tibetan Plateau network for permafrost to characterize satellite-based products errors: An application to soil moisture and freeze/thaw - Jingyao Zheng; Tianjie Zhao; Haishen Lü; Defu Zou; Nemesio Rodriguez-Fernandez; Arnaud Mialon; Philippe Richaume; Jianshe Xiao; Jun Ma; Lei Fan; Peilin Song; Yonghua Zhu; et al. (Remote Sensing of Environment, 2024)

Correction to: Protective Efect of Manganese on Apoptosis and Mitochondrial Function of Heat-Stressed Primary Chick Embryonic Myocardial Cells - Rui Wang; Zhaoguo Shi; Jinlu Li; Defu Tang; Shizhen Qin; Yanli Guo (Biological Trace Element Research, 2024)

Penaeid shrimp counteract high ammonia stress by generating and using functional peptides from hemocyanin, such as HMCs27 - Mingming Zhao; Zhihong Zheng; Chuanqi Wang; Defu Yao; Zhongyang Lin; Yongzhen Zhao; Xiuli Chen; Shengkang Li; Jude Juventus Aweya; Yueling Zhang (Science of The Total Environment, 2023)

Highly efficient removal of Aflatoxin B1 employing a flower-like covalent organic framework-based fiber membrane - Shuning Li; Kang Qin; Yixue Fu; Defu He; Dianpeng Han; Shuang Li; Yu Wang; Shuyue Ren; Yuan Peng; Zhixian Gao (Journal of Environmental Chemical Engineering, 2023)

Toxic effects of environmentally persistent free radicals (EPFRs) on the surface of tire wear particles on freshwater biofilms: The alleviating role after sewage-incubation-aging - Kun Li; Deyue Kong; Xiaojia Xiu; Wanqi Hao; Defu Xu (Chemosphere, 2023)

Investigation on Pb2+ adsorption characteristics by AAEMs-rich biochar in aqueous solution: Performance and mechanism - Jiahao Jiang; Ruiyu Li; Kaixuan Yang; Yuhang Li; Lei Deng; Defu Che (Environmental Research, 2023)

Green synthesis of bimetallic Pd Ag alloy nanoparticles supported on polydopamine-functionalized kaolin for catalytic reduction of 4-nitrophenol and organic dyes - Defu Gan; Zhenyu Wang; Xiaodi Li; Jingzhou Zhou; Ben Dai; Lin Yang; Siqing Xia (Applied Clay Science, 2023)

Novel ship fuel consumption modelling approaches for speed and trim optimisation: Using engine data as auxiliary - Kangli Wang; Defu Zhang; Zhenyu Shen; Wei Zhu; Hongcai Ye; Dong Li (Ocean Engineering, 2023)

Risk factors of vestibular migraine-related brain white matter lesions - Yu Shen; Defu Li; Qian Cao; Mengyao Hu; Zhou Hou; Lijun Xu; Yanping Li; Daojun Hong (Acta Neurologica Belgica, 2023)

DNA origami-mediated plasmonic dimer nanoantenna-based SERS biosensor for ultrasensitive determination of trace diethylstilbestrol - Sen Li; Baodi Shi; Defu He; Huanying Zhou; Zhixian Gao (Journal of Hazardous Materials, 2023)

Dual-drug loaded polysaccharide-based self-healing hydrogels with multifunctionality for promoting diabetic wound healing - Weiwei Tan; Tao Long; Yanzhuo Wan; Bingchen Li; Zhilang Xu; Lei Zhao; Changdao Mu; Liming Ge; Defu Li (Carbohydrate Polymers, 2023)

Synthesis of NaA zeolite from foundry dust and its adsorption capacity of ammonia - Mengqing Wang; Defu Xu; Hui Ma; Bing Li; Alan Howard (Journal of Environmental Management, 2023)

Dynamics and diversity of microbial community in salmon slices during refrigerated storage and identification of biogenic amine-producing bacteria - Yingchang Li; Nan Zhao; Yuanyuan Li; Defu Zhang; Tong Sun; Jianrong Li (Food Bioscience, 2023)

Spatiotemporal variations and driving factors for potential wind erosion on the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Xin Ma; Yadong Liu; Xuchun Yan; Xiaoying Fan; et al. (Science of The Total Environment, 2023)

Water and heat coupling processes and its simulation in frozen soils: Current status and future research directions - Guojie Hu; Lin Zhao; Ren Li; Hotaek Park; Xiaodong Wu; Youqi Su; Georg Guggenberger; Tonghua Wu; Defu Zou; Xiaofan Zhu; Wenxin Zhang; Yifan Wu; et al. (CATENA, 2023)

Activity enhancement of core–shell Pd@mCeO2 catalysts for phenol hydrogenation to cyclohexanone by tuning metal-support interactions - Defu Yin; Renjie Ji; Jingyun Zhang; Shitao Yu; Lu Li; Shiwei Liu; Long Jiang; Ying Liu; Zhanqian Song; Yue Liu (Fuel, 2023)

Microfiber-loaded bacterial community in indoor fallout and air-conditioner filter dust - Yingxin Chen; Xinyu Li; Wei Gao; Yalin Zhang; Aoyun Mo; Jie Jiang; Defu He (Science of The Total Environment, 2023)

Prominent toxicity of isocyanates and maleic anhydrides to Caenorhabditis elegans: Multilevel assay for typical organic additives of biodegradable plastics - Xinyu Li; Yingxin Chen; Wei Gao; Aoyun Mo; Yalin Zhang; Jie Jiang; Defu He (Journal of Hazardous Materials, 2023)

Nutrient released characteristics of struvite-biochar fertilizer produced from concentrated sludge supernatant by fluidized bed reactor - Yingxue Li; Defu Xu; Haizhi Lin; Wenhua Wang; Hong Yang (Journal of Environmental Management, 2023)

DRAXIN as a Novel Diagnostic Marker to Predict the Poor Prognosis of Glioma Patients - Yulong Jia; Zhendong Liu; Xingbo Cheng; Runze Liu; Pengxu Li; Defu Kong; Wenjia Liang; Binfeng Liu; Hongbo Wang; Xingyao Bu; Yanzheng Gao (Journal of Molecular Neuroscience, 2022)
An increasing number of evidences have shown that the carcinogenic effect of DRAXIN plays an important role in the malignant process of tumors, but the mechanism of its involvement in glioma has not yet been revealed. The main aim of this study is to explore the relationship between DRAXIN and the prognosis and pathogenesis of glioma through a large quality of data analysis. Firstly, thousands of tissue samples with clinical information were collected based on various public databases. Then, a series of bioinformatics analyses were performed to mine data from information of glioma samples extracted from several reputable databases to reveal the key role of DRAXIN in glioma development and progression, with the confirmation of basic experiments. Our results showed that high expression of the oncogene DRAXIN in tumor tissue and cells could be used as an independent risk factor for poor prognosis in glioma patients and was strongly associated with clinical risk features. The reverse transcription-quantitative PCR technique was then utilized to validate the DRAXIN expression results we obtained. In addition, co-expression analysis identified, respectively, top 10 genes that were closely associated with DRAXIN positively or negatively. Finally, in vitro experiments demonstrated that knockdown of DRAXIN significantly inhibited proliferation and invasion of glioma cell. To sum up, this is the first report of DRAXIN being highly expressed in gliomas and leading to poor prognosis of glioma patients. DRAXIN may not only benefit to explore the pathogenesis of gliomas, but also serve as a novel biological target for the treatment of glioma.

Protective Effect of Manganese on Apoptosis and Mitochondrial Function of Heat-Stressed Primary Chick Embryonic Myocardial Cells - Rui Wang; Zhaoguo Shi; Jinlu Li; Defu Tang; Shizhen Qin; Yanli Guo (Biological Trace Element Research, 2022)

Long-term soil temperature dynamics of the Kunlun Pass permafrost region on the Qinghai-Tibetan Plateau - Guojie Hu; Lin Zhao; Tonghua Wu; Xiaodong Wu; Ren Li; Xiaofan Zhu; Defu Zou; Junming Hao; Wangping Li (Theoretical and Applied Climatology, 2022)

Decontamination of multiple pollutants from eutrophic river water using iron-modification carbon/zeolite - Hui Ma; Yingxue Li; Defu Xu; Hanxin Tian; Hong Yang (Journal of Soils and Sediments, 2022)

Metabolic reprogramming in crustaceans: A vital immune and environmental response strategy - Zhongyan Wang; Yueling Zhang; Defu Yao; Yongzhen Zhao; Ngoc Tuan Tran; Shengkang Li; Hongyu Ma; Jude Juventus Aweya (Reviews in Aquaculture, 2022)
Most host organisms undergo metabolic changes in response to pathogens, environmental cues or simply to boost their immunity. Metabolic modulation has therefore been exploited by both host and pathogens to outwit the other during host–pathogen interactions. Recent studies have revealed that a growing number of metabolites and metabolic processes in crustaceans are crucial in host–pathogen interactions. Here, we reviewed recent work on metabolic changes during immune response of crustaceans and the metabolic reprogramming that takes place in the host induced by pathogens, environmental cues or as a host strategy to withstand these changes or clear the pathogen. In aquaculture crustaceans, limited studies exist on this subject; hence, we will also highlight themes for possible future research on metabolite reprogramming and how this strategy can be leveraged to improve sustainable aquaculture and enhance crustaceans’ response to pathogens and environmental changes.

Adaptability of organic matter and solid content to Fe2+/persulfate and skeleton builder conditioner for waste activated sludge dewatering - Xiaoran Li; Yafei Shi; Xi Zhou; Lu Wang; Huiqin Zhang; Kewu Pi; Andrea R. Gerson; Defu Liu (Environmental Science and Pollution Research, 2022)

Effects of Chronic Stress on the Fecal Microbiome of Malayan Pangolins (Manis javanica) Rescued from the Illegal Wildlife Trade - Dingyu Yan; Defu Hu; Kaixiang Li; Baocai Li; Xiangyan Zeng; Jinyan Chen; Yimeng Li; Torsten Wronski (Current Microbiology, 2021)

Effects of ammonia on shrimp physiology and immunity: a review - Mingming Zhao; Defu Yao; Shengkang Li; Yueling Zhang; Jude Juventus Aweya (Reviews in Aquaculture, 2020)
The rapid expansion in shrimp farming comes with problems such as inadequate culture technology, disease outbreak, water pollution and other environmental degradation‐related problems. Prominent among these is the level of ammonia, which has been rising steadily in the last couple of years, mainly due to farming practices and other anthropogenic activities, and therefore has had consequent effects on marine life, especially shrimp. While optimal ammonia levels are a good source of nitrogen for marine phytoplankton that increases the level of dissolved oxygen in water as well serves as food for shrimp, high levels of ammonia are harmful to shrimp. When shrimp pond ammonia levels go beyond the tolerance limits, it inhibits chitinase expression, moulting, growth, phenoloxidase and haemolymph antimicrobial activity, thereby attenuating shrimp innate immune response. In this review, we bring together recent information on the effects of ammonia stress on the growth, physiology, biochemistry, ammonia‐metabolizing enzymes and immunity of shrimp. We also propose areas of research that can be explored in the breeding of new ammonia‐tolerant and disease‐resistant shrimp with robust immune and/or physiological systems that could withstand environmental stress and pathogens.

Responses of nitrogen transformation and dissolved oxygen in constructed wetland to biochar and earthworm amendment - Lei Zhou; Jiajun Wang; Defu Xu; Yingxue Li; Bin Yao; Alan Howard (Environmental Science and Pollution Research, 2020)

Association between long-term occupational manganese exposure and bone quality among retired workers - Defu Li; Xiaoting Ge; Zhenfang Liu; Lulu Huang; Yanting Zhou; Peng Liu; Lian Qin; Suzhen Lin; Chaoqun Liu; Qingzhi Hou; Longman Li; Hong Cheng; et al. (Environmental Science and Pollution Research, 2020)

Comparative study of carboxylic acid adsorption on calcite: l-malic acid, d-malic acid and succinic acid - Zhenxuan Li; Jiangtian Xiao; Lidong Huang; Defu Xu; Dagang Liu; Xiaowen Sun; Luji Yu; Hongsheng Wu (Carbonates and Evaporites, 2019)

Effect of earthworm and loach on Typha augustifolia aboveground and root litter residue in an integrated vertical subsurface flow constructed wetland - Yingxue Li; Defu Xu; Dongqin Zhou; Lei Zhou; Alan Howard (Wetlands Ecology and Management, 2019)

Specific roles of Os4BGlu10, Os6BGlu24, and Os9BGlu33 in seed germination, root elongation, and drought tolerance in rice - Ruijuan Ren; Dong Li; Chunyan Zhen; Defu Chen; Xiwen Chen (Planta, 2019)

Regulatory Roles of Peroxisomal Metabolic Pathways Involved in Musk Secretion in Muskrats - Meishan Zhang; Shuang Yang; Minghui Shi; Shumiao Zhang; Tianxiang Zhang; Yimeng Li; Shanghua Xu; Muha Cha; Yuping Meng; Shaobi Lin; Juan Yu; Xuxin Li; et al. (The Journal of Membrane Biology, 2019)

Comparative study of the physicochemical and photocatalytic properties of water-soluble polymer-capped TiO2 nanoparticles - Jinfeng Lei; Lei Deng; Xinying Li; Yongbin Xu; Defu Li; Changdao Mu (Environmental Science and Pollution Research, 2018)

Spatiotemporal changes of freezing/thawing indices and their response to recent climate change on the Qinghai–Tibet Plateau from 1980 to 2013 - Tonghua Wu; Yanhui Qin; Xiaodong Wu; Ren Li; Defu Zou; Changwei Xie (Theoretical and Applied Climatology, 2018)

Isolation, Immobilization, and Degradation Performance of the 17β-Estradiol-Degrading Bacterium Rhodococcus sp. JX-2 - Jingxian Liu; Juan Liu; Defu Xu; Wanting Ling; Shunyao Li; Mindong Chen (Water, Air, & Soil Pollution, 2016)

Chronic Exposure to Perfluorooctane Sulfonate Reduces Lifespan of Caenorhabditis elegans Through Insulin/IGF-1 Signaling - Tiantian Xu; Ping Li; Siyu Wu; Dan Li; Jingxuan Wu; Kathleen M. Raley-Susman; Defu He (Bulletin of Environmental Contamination and Toxicology, 2016)

Air quality improvement during 2010 Asian games on blood coagulability in COPD patients - Zili Zhang; Jian Wang; Meihua Guo; Mingmei Xiong; Qipeng Zhou; Defu Li; Jiaze Shu; Wenju Lu; Dejun Sun (Environmental Science and Pollution Research, 2016)

Purifying capability, enzyme activity, and nitrification potentials in December in integrated vertical flow constructed wetland with earthworms and different substrates - Defu Xu; Jiaru Gu; Yingxue Li; Yu Zhang; Alan Howard; Yidong Guan; Jiuhai Li; Hui Xu (Environmental Science and Pollution Research, 2016)

Acteoside reduces testosterone by inhibiting cAMP, p450scc, and StAR in rat Leydig cells - Shuqiang Liu; Junwen Zhang; Weixuan Li; Tianxiang Zhang; Defu Hu (Molecular & Cellular Toxicology, 2015)

Influence of UV radiation on chlorophyll, and antioxidant enzymes of wetland plants in different types of constructed wetland - Defu Xu; Yinjuan Wu; Yingxue Li; Alan Howard; Xiaodong Jiang; Yidong Guan; Yongxia Gao (Environmental Science and Pollution Research, 2014)

Evaluation of fecal DNA preservation and extraction methods in Przewalski’s horse - Gang Liu; Sen Zang; Linhai Li; Xiaolong Hu; Shasha Zhao; Kai Li; Defu Hu (Conservation Genetics Resources, 2014)

Isolation and characterization of microsatellite loci from Gasterophilus pecorum (Diptera: Gasterophilidae) - Fang Cheng; Jianmei Yang; Dong Zhang; Defu Hu; Hongjun Chu; Jie Cao; Feng Jiang; Lan Bu; Kai Li (Conservation Genetics Resources, 2014)

Influence of earthworm Eisenia fetida on removal efficiency of N and P in vertical flow constructed wetland - Defu Xu; Yingxue Li; Alan Howard (Environmental Science and Pollution Research, 2013)

Temporal and spatial variations of global solar radiation over the Qinghai–Tibetan Plateau during the past 40 years - Ren Li; Lin Zhao; Tonghua Wu; Yongjian Ding; Yufei Xin; Defu Zou; Yao Xiao; Yongliang Jiao; Yanhui Qin; Linchan Sun (Theoretical and Applied Climatology, 2013)

Natural anthocyanins from phytoresources and their chemical researches - Xinying Li; Hongyan Ma; Huilian Huang; Defu Li; Shun Yao (Natural Product Research, 2013)

Feasibility Study on Quantitative Measurements of Singlet Oxygen Generation Using Singlet Oxygen Sensor Green - Huiyun Lin; Yi Shen; Defu Chen; Lisheng Lin; Brian C. Wilson; Buhong Li; Shusen Xie (Journal of Fluorescence, 2013)